在数列 $\left\{a_n\right\}$ 中, $a_1=2, a_2=6, a_3=12$, 且数列 $\left\{a_{n+1}-a_n\right\}$ 是等差数列.
(1) 求 $\left\{a_n\right\}$ 的通项公式;
(2) 若 $b_n=a_n \cos n \pi$, 求数列 $\left\{b_n\right\}$ 的前 $n$ 项和 $T_n$.
【答案】 解: (1) 因为 $a_2-a_1=4, a_3-a_2=6$, 所以 $a_3+a_2-\left(a_2-a_1\right)=2$,
所以数列 $\left\{a_{n+1}-a_n\right\}$ 是首项为 4 , 公差为 2 的等差数列, 所以 $a_{n+1}-a_n=4+2(n-1)=2 n+2 . \cdots \cdots \cdots 2$ 分 当 $n \geqslant 2$ 时, $a_n=\left(a_n-a_{n-1}\right)+\left(a_{n-1}-a_{n-2}\right)+\cdots+\left(a_2-a_1\right)+a_1=2 n+2(n-1)+\cdots+2 \times 2+2=n^2+n$.
当 $n=1$ 时, $a_1=2$ 也满足上式. 所以 $a_n=n^2+n$.
(2) 由 (1) 知, $b_n=a_n \cos n \pi=(-1)^n\left(n^2+n\right)=(-1)^n n(n+1)$,
当 $n=2 k, k \in \mathbf{N}^*$ 时,
$T_n=-1 \times 2+2 \times 3-3 \times 4+4 \times 5-\cdots-(n-1) n+n(n+1)=2(2+4+\cdots+n)=\frac{n(n+2)}{2} ; \cdots \cdots \cdots \cdots \cdots 9$ 分
当 $n=2 k-1, k \in \mathbf{N}^*$ 时,
$T_n=T_{n+1}-b_{n+1}=\frac{(n+1)(n+3)}{2}-(n+1)(n+2)=-\frac{(n+1)^2}{2}$,
11 分
所以 $T_n=\left\{\begin{array}{l}\frac{n(n+2)}{2}, n=2 k, k \in \mathbf{N}^*, \\ -\frac{(n+1)^2}{2}, n=2 k-1, k \in \mathbf{N}^* .\end{array}\right.$


系统推荐